2011
DOI: 10.5194/nhess-11-3197-2011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, numerical and analytical modelling of a newly developed rockfall protective cable-net structure

Abstract: Abstract. An innovative configuration of pocket-type rockfall protective cable-net structure, known as Long-span Pocket-type Rock-net (LPR), has been developed in Japan. The global performance of the proposed system was initially checked by the experimental (full-scale) modelling. Given the various limitations of the physical experiments, particularly for the parametric study to have a detailed understanding of the newly developed system, a reliable and simplified method of numerical modelling is felt necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The system performed well; no damage was recorded and it was confirmed that the instrumented forces developed in the cables were well below the safety margin defined by the (yet conservative) Allowable Stress Design philosophy (see Dhakal et al, 2011a for further details). Moreover, given the very important condition that the targeted sites of LPR application typically have very limited space between the hillslope and the road-carriageway the former verification implied that the global out-of-plane displacement response of the wire-net (which may be simply referred to as "displacement" hereinafter) might be more vital in evaluating the performance of the structure.…”
Section: A Brief Review Of the Companion Papermentioning
confidence: 94%
See 3 more Smart Citations
“…The system performed well; no damage was recorded and it was confirmed that the instrumented forces developed in the cables were well below the safety margin defined by the (yet conservative) Allowable Stress Design philosophy (see Dhakal et al, 2011a for further details). Moreover, given the very important condition that the targeted sites of LPR application typically have very limited space between the hillslope and the road-carriageway the former verification implied that the global out-of-plane displacement response of the wire-net (which may be simply referred to as "displacement" hereinafter) might be more vital in evaluating the performance of the structure.…”
Section: A Brief Review Of the Companion Papermentioning
confidence: 94%
“…Lam et al, 2010;Yang et al, 2011;Dhakal et al, 2011a;Ali et al, 2011). As such, the wire-net is the major structural component of the rockfall restraining LPR system and contributes more than 70 % to the total mass.…”
Section: Idea and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…This explicit program is used to capture dynamic and extremely rapid responses of structures to severe impact loads [9]. The numerical model is primarily based on simplifications of the material properties of fence components, such as the wire ropes (Fig.…”
Section: Numerical Analysis Of the Developed Prototypementioning
confidence: 99%